Late 3d Metal-Catalyzed (Cross-) Dimerization of Terminal and Internal Alkynes - Weber, Sebastian M.; Hilt, Gerhard (Frontiers in Chemistry, 2021)
This review will outline the recent advances in chemo-, regio- and stereoselective (cross)-dimerization of terminal alkynes to generate 1,3-enynes using different types of iron and cobalt catalysts with altering oxidation states of the active species. In general, the used ligands have a crucial effect on the stereoselectivity of the reaction, e.g. bidentate phosphine ligands in cobalt catalysts can generate the E-configured head-to-head dimerization product, while tridentate phosphine ligands can generate either the Z-configured head-to-head dimerization product or the branched head-to-tail isomer. Furthermore, the hydroalkynylation of silyl-substituted acetylenes as donors to internal alkynes as acceptors will be discussed using cobalt and nickel catalysts.